The Influence of Financial Literacy on Financial Inclusion in Indonesia with Fintech as a Mediator - Jhonny Se (Politeknik Negeri Bengkalis, 2023)
This study aims to examine the relationship between financial literacy and financial inclusion in Indonesia, with fintech as a mediating factor. Financial literacy plays a crucial role in enabling individuals to make informed financial decisions and effectively participate in the formal financial system. Fintech, on the other hand, has emerged as a transformative force, providing innovative financial services to previously underserved populations. This research investigates whether financial literacy positively impacts financial inclusion and whether fintech acts as a mediator in this relationship. The study utilizes a quantitative research design, employing survey data collected from a representative sample of Indonesian residents. The findings of this research will contribute to our understanding of the importance of financial literacy and fintech in promoting financial inclusion and provide insights for policymakers, financial institutions, and fintech providers.